Small Molecule Drug C381 Attenuates Brain Vascular Damage Following Repetitive Mild Traumatic Injury - Lulin Li; Andy Nguyen; Brian Zhao; Ryan Vest; Lakshmi Yerra; Bryan Sun; Jian Luo (Neurotrauma Reports)
Traumatic brain injury (TBI) remains a significant public health concern, with no effective therapeutic interventions to ameliorate the enduring consequences. The prevailing understanding of TBI pathophysiology indicates a central role for vascular dysfunction. Transforming growth factor-β (TGF-β) is a multifunctional cytokine crucial for vascular development. Aberrant TGF-β signaling is implicated in vascular pathologies associated with various neurological conditions. We recently developed a novel small molecule drug, C381, a TGF-β activator with the ability to restore lysosomal function. Here we used a mouse model of repetitive mild TBI (mTBI) to examine whether C381 would attenuate vascular injury. We first employed RNA-seq analysis to investigate the gene expression patterns associated with mTBI and evaluated the therapeutic potential of C381 in mitigating these changes. Our results demonstrate distinct mTBI-related gene expression signatures, prominently implicating pathways related to vascular integrity and endothelial function. Notably, treatment with C381 reversed these mTBI-induced gene expression changes. Immunohistochemical analysis further corroborated these findings, revealing that C381 treatment attenuated vascular damage in mTBI-affected brain tissue. These findings strongly support the potential clinical usefulness of C381 as a novel therapeutic intervention for mTBI.